2020
DOI: 10.1186/s13018-020-01960-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of suprapatellar versus infrapatellar approaches of intramedullary nailing for distal tibia fractures

Abstract: Background This study aimed to analyze and compare the clinical and functional outcomes of distal tibia fractures treated with intramedullary nailing (IMN) using the suprapatellar (SP) and infrapatellar (IP) surgical approaches. Methods A retrospective analysis was performed in 63 patients with distal fractures that were treated with IMN between August 2014 and August 2018. A total of 27 and 36 patients underwent IMN using the SP and IP techniques, respectively. The surgical time, blood loss, closed reductio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 27 publications
1
28
0
4
Order By: Relevance
“…Malalignment is one of the noted complications to intramedullary nailing of the tibia. Courtney [14,27]. This has also been observed in extra-articular proximal tibia fractures as per Kulkarni et al [28].…”
Section: Discussionmentioning
confidence: 66%
“…Malalignment is one of the noted complications to intramedullary nailing of the tibia. Courtney [14,27]. This has also been observed in extra-articular proximal tibia fractures as per Kulkarni et al [28].…”
Section: Discussionmentioning
confidence: 66%
“…In another retrospective cohort study comparing 74 SP and 51 HFIP nails, Hague et al suggested that the SP technique may enhance coronal plane alignment with the intramedullary nailing of DTFs [ 32 ]. Lu et al analyzed and compared the clinical and functional endpoints of DTFs managed with IMN, and the authors reported that the malalignment rate in SP patients (4.8%, 2/42) was considerably diminished compared to HFIP patients (14.3%,8/56) [ 14 ]. In the current study, the malalignment rate of SEIP patients was 4.7%, which was markedly reduced relative to HFIP patients, which corroborated the radiographical outcomes of a prior investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The following patients were selected for analysis: those with extraarticular fractures (OTA 43-A) and (OTA 43-C1 and C2) with a nondisplaced intraarticular fracture line [ 8 ]. Moreover, we only included fractures with major fracture lines located within 12 cm of the distal tibial plafond [ 14 ]. The following patients were eliminated from the analysis: those with a fracture occurring too distal to achieve proper fixation of four cortices using distal interlocking screws [ 5 ] and those with an ipsilateral proximal tibia fracture or knee injury, prior knee or ankle surgery preexisting ankle arthrodesis, and pathological fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The tibial IMN was inserted under a standard technique in all sawbones ( Lu et al, 2020 ). An unstable extra-articular proximal tibial fractures (OTA/AO 41A2) were created in all sawbones.…”
Section: Methodsmentioning
confidence: 99%